2018
DOI: 10.1111/1556-4029.13816
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Polydimethylsiloxane Condom Lubricants

Abstract: Polydimethylsiloxane (PDMS) is commonly used to lubricate condoms. The detection of PDMS on swabs from complainants can be used to support an allegation of sexual assault. Previous research has focused on establishing analytical techniques for detecting PDMS. This research examined the persistence of PDMS on the penis, in the vagina, in the mouth, and on skin. The longest PDMS detection times were 20 h on the penis, 35 h in the vagina, and 52 h on skin. PDMS was detected up to 4 h in the mouth if the participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Because of its optical clearance, PDMS has been used in so called suspended particle devices for smart window applications [14][15][16]. Applications also include, but not limited to defoamers [17], contact lenses [18], waterrepellent coatings [19], cosmetics [20], lubricants [21], and many others. However, in this review we will focus on adhesive and mechanical properties of PDMS.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its optical clearance, PDMS has been used in so called suspended particle devices for smart window applications [14][15][16]. Applications also include, but not limited to defoamers [17], contact lenses [18], waterrepellent coatings [19], cosmetics [20], lubricants [21], and many others. However, in this review we will focus on adhesive and mechanical properties of PDMS.…”
Section: Introductionmentioning
confidence: 99%
“…A survey on 841 case reports from three law enforcement agencies in the United States showed that the prevalence rate of condom use in sexual assaults ranged from 11.7 to 15.6% (2). Consequently, since many years, and increasingly lately, Courts have been requesting the examination of the intimate swabs of the victims, seeking for traces of condom lubricants and/or other sexual lubricants (3–6), also because several works showed that the persistence of condom lubricants can be quite significant, up to 52 or 25 h on the skin or in the vagina of the victim, respectively, and up to 20 h on the penis of the assailant (3,7–10). Given the limited number of swabs that may be collected, in certain circumstances, from a complainant during her medical examination, the subsequent decision concerning which swabs to analyze for the presence of DNA versus condom lubricants is pivotal and can heavily impact on the outcome of the case.…”
mentioning
confidence: 99%
“…Maynard et al in 2001 analyzed 50 lubricants from condoms and personal lubricant products using a series of instrumental techniques including diffuse reflectance infrared Fourier‐transform spectroscopy (DRIFTS), GC‐MS, liquid chromatography–mass spectrometry (LC‐MS), and pyrolysis–gas chromatography–mass spectrometry (Py‐GC‐MS) (10). Indeed, a common feature of most proposed protocols devised to identify condom‐related compounds is that complementary methods should be also applied (5,7,11).…”
mentioning
confidence: 99%
See 2 more Smart Citations